A method to prepare linamarin microparticles and a formulation derives thereof. - Abdullah, Norhafizah; Ahmadun, Fakhru'l-Razi (2007)

(untitled)
A controlled release pharmaceutical formulation for cancer treatment comprising linamarin or its derivatives encapsulated in a matrix of poly(D,L-lactide-c-glycolide) and poly vinyl alcohol prepared in a double emulsion form.